Understanding antimicrobial prescription practices: Insights from small animal veterinarians in North Macedonia - Shikoska, Ivana; Cvetkovikj, Aleksandar; Nikolovski, Martin; Cvetkovikj, Iskra (Sciendo, 2024)
Antimicrobial resistance (AMR) is an increasing global concern in small animal veterinary practices. The overuse and misuse of antimicrobials in companion animals can contribute to the spread of AMR between animals and humans. This study aimed to assess small animal veterinarians’ knowledge, attitudes, and behaviors towards antimicrobial use (AMU) and AMR in North Macedonia. A web-based questionnaire was developed, including questions addressing demographics, owner influence on antibiotic prescription and prescribing practices. The response rate of the small animal veterinarians was 47.50% (57/120), with most of them (84.20%) having 1-15 years of work experience. Pearson’s chi-square test of independence was used for contingency tables that met the chi-square assumption, and Fisher’s exact test was conducted for contingency tables that did not. Most veterinarians responded that they had perceived pressure and direct demands from pet owners to prescribe antimicrobials (35.09% frequently, 45.61% occasionally). In the survey, 50.77% of the veterinarians reported frequently administering antibiotics without conducting bacteriological or antimicrobial susceptibility testing. They typically resorted to these tests in cases with recurrent infections, such as skin infections (19.63%), or when empirical therapy is ineffective (14.72%). Based on the findings, it can be concluded that veterinarians play a crucial role in tackling the AMR in North Macedonia. The lack of stewardship programs or guidelines for responsible antimicrobial use in companion animals is a critical issue that requires urgent attention, emphasizing the vital role of veterinarians in combating AMR.
Keywords: stewardship, companion animals, guidelines, survey, awareness